The Women of Karbala: Ritual Performances and Symbolic Discourses in Modern Shi`i Islam by Kamran Scot Aghaie, ed. (Austin: University of Texas Press, 2005. 304 pages.) (American Journal of Islam and Society, 2006)
This beautifully produced work provides a gendered reading of the centralityof the Karbala commemorations among Shi`i communities. There isa strong Persian(ate) bias in the selections (only two papers really deal withpractices in an Arab context). However, it represents the maturity of the stateof Shi`i studies, having moved beyond the sensationalism of political obsessionsfollowing the Iranian revolution of 1979 and the textually basedOrientalism of an earlier generation to considerations of actual practices,performances, understanding of texts, and enactments of doctrines. The Women of Karbala is a significant contribution to the study of Shi`iIslam in practice. Most of the papers are based on anthropological fieldworkin majoritarian communities. The collection could have benefited from somemore historical studies (there are two studies on the Qajar period), textualstudies, and examinations of Arab communities, as well as the increasingsignificance of the Shi`i diasporic communities in Europe and North America(one paper does nod in that direction). Another feature that would haveenhanced the collection would be to interpret Shi`i more widely. For example,there is one paper on Bohra practices but none on the Zaydis and recentdevelopments in the Yemeni highlands that have made Shi`i commemorationscritical junctures of conflict ...